Progress, Challenges and Prospects of Biomass-Derived Lightweight Carbon-Based Microwave-Absorbing Materials - Xujing Ren; Meirong Zhen; Fuliang Meng; Xianfeng Meng; Maiyong Zhu (Nanomaterials)
The widespread use of electronic devices in daily life, industry and military has led to a large amount of electromagnetic pollution, which has become an increasingly serious security issue. To eliminate or mitigate such risks and hazards, various advanced microwave absorption technologies and materials have been reported. As a new type of microwave absorber, biomass-derived carbon-based materials have received extensive attention. They have the characteristics of low cost, easy preparation, high porosity and environmental friendliness while retaining the advantageous adjustable dielectric properties, high conductivity and good stability of traditional carbon materials. The development of biomass microwave-absorbing materials not only provides a new idea for solving electromagnetic radiation but also helps to create an environmentally friendly and harmonious environment. Herein, various biomass-derived carbon-based microwave-absorbing materials (MAMs) including plant shells, plant fibers and other potential biomass materials are generalized and discussed including their preparation technology, microstructure design and so on. The two critical factors affecting microwave absorption properties, impedance matching and attenuation characteristics, are analyzed in detail. Finally, the confronting challenges and future development prospects of biomass-based microwave-absorbing materials are pointed out.